2019
DOI: 10.1109/tcbb.2018.2827373
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for LncRNA-Disease Association Prediction Based on an lncRNA-Disease Association Network

Abstract: An increasing number of studies have indicated that long-non-coding RNAs (lncRNAs) play critical roles in many important biological processes. Predicting potential lncRNAdisease associations can improve our understanding of the molecular mechanisms of human diseases and aid in finding biomarkers for disease diagnosis, treatment, and prevention. In this paper, we constructed a bipartite network based on known lncRNA-disease associations; based on this work, we proposed a novel model for inferring potential lncR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 49 publications
0
52
0
Order By: Relevance
“…To show the prediction ability of the RFLDA, we compare it with several excellent LDA prediction models, such as SIMCLDA [33], Ping's method [18], MFLDA [31], LDAP [39], CNNLDA [44], and GCNLDA [45]. The AUCs and AUPRs of all LDA prediction models are shown in Table 1.…”
Section: Performance Comparison With Other Prediction Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…To show the prediction ability of the RFLDA, we compare it with several excellent LDA prediction models, such as SIMCLDA [33], Ping's method [18], MFLDA [31], LDAP [39], CNNLDA [44], and GCNLDA [45]. The AUCs and AUPRs of all LDA prediction models are shown in Table 1.…”
Section: Performance Comparison With Other Prediction Modelsmentioning
confidence: 99%
“…Xiao et al proposed a paths of fixed lengths based LDA prediction model (BPLLDA) [17]. Ping et al inferred potential LDAs by an experimentsupported LDA network [18]. Fan et al implemented a RWR based LDA prediction model (IDHI-MIRW) by combining the positive pointwise mutual information with multiple heterogeneous information [19].…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we will further use the receiver operating characteristic curve (ROC curve) to evaluate the performance of TGSO. Studies show that the larger the area under the ROC curve (AUC), the better the performance of the model, and if AUC=0.5, it means a random performance [55][56][57]. In the three kinds of yeast cell databases including the DIP, Krogan and GAVIN databases, the proportion of key proteins is very small, and the proportion of non-essential proteins and essential proteins is about 3 to 1.…”
Section: Validation By Precision-recall Curves and Roc Curvesmentioning
confidence: 99%
“…lncRNAs play critical roles in various human biological processes, such as chromatin modification, cell differentiation, proliferation and apoptosis, translational and post-translational regulation. Moreover, the abnormally expressed lncRNAs are involved in the occurrence and development of a variety of human diseases [27]. In recent years, more and more evidence has shown that lncRNAs are abnormally expressed in ovarian cumulus cells and/or GCs of PCOS patients [9,28,29].…”
Section: Lncrnasmentioning
confidence: 99%